Polymersomes and Wormlike Micelles Made Fluorescent by Direct Modifications of Block Copolymer Amphiphiles - Karthikan Rajagopal; David A. Christian; Takamasa Harada; Aiwei Tian; Dennis E. Discher (International Journal of Polymer Science)
Wormlike micelles and vesicles prepared from diblock copolymers are attracting great interest for a number of technological applications. Although transmission electron microscopy has remained as the method of choice for assessing the morphologies, fluorescence microscopy has a number of advantages. We show here that when commercially available fluorophores are covalently attached to diblock copolymers, a number of their physicochemical characteristics can be investigated. This method becomes particularly useful for visualizing phase separation within polymer assemblies and assessing the dynamics of wormlike micelles in real time. Near-IR fluorophores can be covalently conjugated to polymers and this opens the possibility for deep-tissue fluorescence imaging of polymer assemblies in drug delivery applications.